Hormonal Protocols for the Synchronization and Induction of Synchronized Estrus in Dairy Ewes Kept under Tropical Conditions - Silva Lombardo, Higor Nascimento; Santos Monteiro, Clara Ana; Delgado, Karina Frensel; Pinna, Aline Emerim; Vasconcelos, Carlos Otávio de Paula; Garcia Nogueira, Luiz Altamiro; Brandão, Felipe Zandonadi; Balaro, Mário Felipe Alvarez (Acta Scientiae Veterinariae, 2020)
Background: Lacaune is an important sheep breed and shows reproductive seasonality which affects dairy product supply. The most common hormonal protocols are based on progesterone-releasing devices in order to reach reproductive activity. Due to international consumer demand for natural, green, and clean methods, such issues encourage the minimal or absent use of synthetic hormones in livestock. In this sense, the present study tested the efficiency of induction and estrus synchronization protocols in lacaune ewes, considering: application interval of synthetic prostaglandin at the breeding season; length of synthetic progesterone exposure; and eCG dose at the outbreeding season. Materials, Methods & Results: In study 1, 52 ewes were submitted to estrus synchronization protocol using two doses of d-cloprostenol 7 or 9 days apart. In study 2, 47 ewes were submitted to estrus induction protocol using an intravaginal device containing 60 mg of medroxyprogesterone acetate maintained for 6, 9, or 12 days. In study 3, 46 ewes were submitted to synchronized estrus induction protocol using intravaginal progesterone device for six days. On the fifth day, d-cloprostenol and 300 IU or 400 IU of eCG were administered. For all studies, signs of estrus beginning/ending were recorded and natural mating was performed. After 30 days, transrectal ultrasound was performed for pregnancy diagnosis. In study 1, groups presented similar rate of estrus behavior (78.8%) and pregnancy (average 75.6%). Meanwhile, compared to G9days (37.8 ± 7.2 h), interval between the second dose of prostaglandin and beginning of estrus was smaller in G7days (31.5 ± 7.8 h). No difference was found among variables studied in study 2 (P > 0.05), nevertheless the SD for the estrus duration was shorter (P < 0.05) in G6days and G12 days when compared with the G9days. Equally, the SD for the interval between sponge withdrawal and beginning and end of estrus was shorter (P < 0.05) in G12days when compared with the G9days. The pregnancy rate, at 30 days, was 71.1%. With regards to study 3, there was no effect of parturition order on sexual behavior between experimental groups (P > 0.05). Equally, no differences were found between variables studied (P > 0.05). The pregnancy rate was 52.2% and number of concepts was 1.5 ± 0.6. Discussion: This paper provides important data on estrus synchronization protocols in dairy sheep kept under tropical conditions. In study 1, both d-cloprostenol protocols were efficient in synchronizing estrus of dairy ewes and reached a fair pregnancy rate. Therefore, it was demonstrated that a d-cloprostenol treatment was a viable alternative to a progestogen treatment, commonly used for estrus synchronization in ewes even during the breeding season. In study 2, all protocols (6, 9 and 12 days of exposure to synthetic progesterone) were efficient in inducing and synchronizing estrus in dairy ewes during the outbreeding season. Therefore, considering not only its efficiency but also the reduction of damage to the vaginal microbiota, the authors strongly encourage the use of the 6-day synthetic progesterone exposure protocol. The third study showed that it is possible to reduce the eCG dose (400 to 300 IU) in dairy ewes while maintaining protocol efficiency, saving 25% of the farmer spending, and avoiding high doses that are related to immune resistance and lower progressive fertility response to IA. In conclusion, the present study verified the efficiency of different hormonal protocols applied for dairy Lacaune ewes kept under tropical conditions, demonstrating that it is possible to decrease: (i) the interval between prostaglandin applications for 7 days apart during the breeding season; (ii) the length of exposure to synthetic progesterone for 6 days; and (iii) the eCG dose to 300 IU during the outbreeding season.